2015
DOI: 10.1200/jco.2015.33.3_suppl.177
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRINOX as first-line therapy in patients with metastatic gastroesophageal cancers (GEC).

Abstract: 177 Background: Adenocarcinomas of the distal esophagus, gastroesophageal junction and stomach (GEC) remain challenging cancers to treat. Unfortunately, 80-90% of newly diagnosed patients (pts) present with advanced disease where the overall median survival (mOS) is less than 1 year. Discouragingly, various common first-line metastatic regimens have similar overall response rates (ORR) (30-40%; and 47% for HER2+ with trastuzumab). Given results within other GI tumors, FOLFIRINOX was administered to pts with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Based on these results, a phase I study is ongoing combining weekly CRLX101 in combination with fluorouracil/leucovorin/oxaliplatin combination chemotherapy (modified FOLFOX6) in advanced solid tumors including gastrointestinal cancers (Clinicaltrials.gov NCT02648711). Phase II studies of the triplet combination of irinotecan/fluorouracil/oxaliplatin (FOLFOXIRI or FOLFIRINOX) have demonstrated promising ORRs of >60% as first-line therapy for advanced gastric cancer (19)(20)(21). As such, the combination of CRLX101 with mFOLFOX6 could be promising in gastroesophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, a phase I study is ongoing combining weekly CRLX101 in combination with fluorouracil/leucovorin/oxaliplatin combination chemotherapy (modified FOLFOX6) in advanced solid tumors including gastrointestinal cancers (Clinicaltrials.gov NCT02648711). Phase II studies of the triplet combination of irinotecan/fluorouracil/oxaliplatin (FOLFOXIRI or FOLFIRINOX) have demonstrated promising ORRs of >60% as first-line therapy for advanced gastric cancer (19)(20)(21). As such, the combination of CRLX101 with mFOLFOX6 could be promising in gastroesophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, FOLFIRINOX has been studied in other settings of PDAC as well as other gastrointestinal cancers, with promising response rates in patients who are able to tolerate the regimen. [ 32 - 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Outside of GEA, FOLFIRINOX has emerged as a standard of care for pancreatic cancer in both the resectable and metastatic setting 13,14 . Additionally, there is a growing body of literature evaluating the e cacy of this regimen in gastroesophageal and gastric cancers [15][16][17] . A pooled analysis of two ongoing Phase II trials of FOLFIRINOX in the rst line metastatic setting for GE junction cancers demonstrated an overall response rate (ORR) of 62.5% 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a growing body of literature evaluating the e cacy of this regimen in gastroesophageal and gastric cancers [15][16][17] . A pooled analysis of two ongoing Phase II trials of FOLFIRINOX in the rst line metastatic setting for GE junction cancers demonstrated an overall response rate (ORR) of 62.5% 15 . In a recently published phase II trial of advanced GEA, among ERBB2-negative patients treated with FOLFIRINOX alone, the ORR was 61%, with a median overall survival of 15.5 months.…”
Section: Introductionmentioning
confidence: 99%